Growing and characterization of YBaCo2O5 thin films using dc sputtering technique (2015)
The present thesis deals with the investigation of the perovskite related complex cobaltite YBaCo2O5+δ in thin film form. The YBaCo2O5+δ thin films were grown through dc sputtering technique and were characterized after their physical properties using standard characterization techniques. The motivation for growing thin films is the lacking information concerning the physicochemical behavior of the compound at nano-scale dimensions and the potential applications in gas sensors. The first crucial step to obtain high-quality thin films is the fabrication of high-quality YBaCo2O5+δ targets. In doing so, polycrystalline YBaCo2O5+δ samples were synthesized either by polymeric precursor method or standard solid-state reaction. The polycrystalline samples were carefully characterized according their structural, morphological, electrical, and magnetic properties using standard characterization techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), vibrating sample magnetometry and electric transport measurements. The achieved results allow one to determine which of the routes is more suitable for obtaining the compound with the desired phase and meaningless concentration of foreign phases. This information is then used for fabricating the targets of the compound by pressing the powders and subsequent sinter at high temperatures. YBaCo2O5+δ thin films are then sputtered from these targets on (001)-oriented SrTiO3 substrates. The substrate temperature is varied between 750 and 850 °C in order to optimize this important growing parameter. Similar to the polycrystalline material, the films are characterized after their structural, morphological, electrical and magnetic properties using standard characterization methods mentioned above. Additional optical and dielectric characterization of the thin films is performed using UV-visible complex impedance spectroscopy. The results achieved both on polycrystalline and thin film samples are evaluated allowing one to draw important conclusions about the fascinating behavior the complex system.